Persepsi Mahasiswa Tentang Pengaruh Kompetensi Pedagogik Dosen Terhadap Motivasi Serta Minat Belajar Bahasa Jepang - Framesti, Aisyah Jingga; Karnawati, Rita Agustina (KIRYOKU, 2025)
This study aims to examine students' perception of the influence of lecturers' pedagogic competence on motivation and interest in learning Japanese. The sample in this study is all students of the Japanese Language Education Study Program at University of Muhammadiyah Prof. DR. Hamka. This study uses a quantitative approach with a survey design and data collected through a structured questionnaire. Data were analyzed using SPSS path analysis method. The results of the path analysis showed that the pedagogic competence of lecturers had a significant influence on student learning motivation with a significance value of 0.000 (<0.05) and a direct influence coefficient of 0.730. However, the pedagogic competence of lecturers did not have a significant direct influence on students' learning interest with a significance value of 0.070 (>0.05) and a direct influence coefficient of 0.138. On the other hand, learning motivation had a significant effect on learning interest with a significance value of 0.000 and a direct influence coefficient of 0.763. Furthermore, the results of the path analysis showed that the indirect influence of lecturers' pedagogic competence on learning interest through learning motivation was greater than the direct influence, with a value of 0.556 compared to 0.138. Thus, it can be concluded that the pedagogic competence of lecturers plays an important role in increasing students' learning motivation, which ultimately has an impact on their interest in learning Japanese.